Quel cadre d'analyse de l'activité motrice de l'élève en EPS ? Étude de cas en enseignement scolaire de la natation - Caroline Ganière; Marc Cizeron (Nantes Université, 2015)
The aim of the study is about developing knowledge to allow teachers to analyze pupils' motor activity in scholar situations they provide, in order to be able to guide their learning. Conducted in scholar teaching of swimming, the study is interested in the analysis of pupils' motor organization considered as a gestalt ie as an (auto) organized and meaning form. Developing an analysis which associate formal and functional aspects of pupils' activity, the results highlight the motor organization coherence of two pupils from separate levels of skills.